Rekomendasi Perbaikan Infrastruktur TI di SMK Berdasarkan Evaluasi Tingkat Kematangan dengan Framework Cobit 4.1 - Ariyadi, Dwiyono; Kusbandono, Hendrik; Astuti, Indah Puji (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The transfer of management from SMK(SMK) in 2017 by the East Java Provincial Government has an impact on many things. One of them is the need for media for communication. Information technology (IT) infrastructure in Vocational Schools is a connecting between Vocational Schools and the East Java Provincial Education Office. IT facilities can streamline and streamline communication between the Office of Education and Vocational Schools in various regions. To find out the state of IT infrastructure in Vocational Schools in Madiun Regency, there is a need to measure the maturity level of IT infrastructure in SMK. One popular IT governance evaluation framework used is COBIT. With the COBIT framework guidelines can assess current conditions, as well as expectations of what will be achieved. The results of the gap will be used as a basis for recommendations for improvements to what stages have not been in line with expectations. The results of the maturity level of management of IT infrastructure in Vocational High Schools at each school on average at AI3 sub domain are at level 2, while AI5 sub domains are at level 1. As for the situation in AI3 sub domains, there are still some who care about the importance of IT infrastructure policy, responsibility for infrastructure management is still limited to individual intuition, as well as the absence of measurement of the results of the objectives whether it has been achieved. While AI5 sub domain is management has begun to identify procedures for collaboration with IT infrastructure suppliers, there are standard criteria for the selection of IT infrastructure suppliers, and there are fundamental objectives for IT infrastructure supplier contract management.